Degenerate nonlinear boundary-value problems - Boichuk, О. A.; Shehda, L. M.; Бойчук, О. А.; Шегда, Л. М. (Institute of Mathematics, NAS of Ukraine, 2009)
We establish necessary and sufficient conditions for the existence of solutions of weakly nonlinear degenerate boundary-value problems for systems of ordinary differential equations with a Noetherian operator in the linear part. We propose a convergent iterative procedure for finding solutions and establish the relationship between necessary and sufficient conditions.